Curcumin Enhances Antimigration of Pentagamavunon-1 by Suppressing MMP-2 and MMP-9 Expression in Triple-Negative (4T1) and Luminal A (T47D) Breast Cancer Cells - Desty Restia Rahmawati; Edy Meiyanto; Riris Istighfari Jenie; Arief Nurrochmad (Indonesian Biomedical Journal)
BACKGROUND: Breast cancer remains the leading cause of cancer death worldwide. Migration and invasion of cancer cells are still crucial stages in the metastasis process, highlighting the urgent need for treatments that target both proliferation and metastatic progression. Curcumin and its synthetic analogue, pentagamavunon (PGV)-1, exhibit antiproliferative effects in breast cancer cells. However, the effects of combining curcumin and PGV-1 on cancer cell migration have not yet been explored. Therefore, this study was conducted to examine the antimigratory effects of curcumin and PGV-1 combination on 4T1 and T47D breast cancer cells.